Strategi Transformasi Digital UMKM Berbasis Inovasi Pemasaran dalam Meningkatkan Resiliensi Ekonomi Masyarakat Lokal di Purwasari Karawang Jawa Barat - Citra Anisa Tika Putri; Zulfa Zakiatul Hidayah; Maharina Maharina; Robby Ewangga (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
This study is motivated by the low level of digital transformation and marketing innovation among MSMEs amid rapid digital economic development. MSMEs play a vital role in local economic growth but still face limitations in technology adoption that affect competitiveness and economic resilience. This research aims to analyze MSME digital transformation strategies based on marketing innovation in improving local economic resilience in Purwasari, Karawang. A descriptive qualitative method was used through interviews, observation, and documentation. The findings show that digital transformation is still in the early stage and not yet integrated into business strategy, while marketing innovation remains low, indicated by limited creativity, weak branding, and suboptimal digital utilization. This condition results in moderate economic resilience, where MSMEs can survive but not grow optimally. The study concludes that digital transformation and marketing innovation are important in strengthening MSME economic resilience, but require improvements in digital literacy, human resources capacity, and a more structured digital ecosystem.